A re-evaluation of Stuart's police officer stigma scale: Measuring mental health stigma in first responders - Burzee, Zachery; Bowers, Clint; Beidel, Deborah (Frontiers in Public Health, 2022)
Stigma about mental illness is often identified as one of the most prominent obstacles to seeking mental health services. This seems to be particularly true among first responders. Unfortunately, the research regarding stigma in first responders is lacking. This may be due, in part, to the absence of appropriate measurement tools to allow such research. Police Officer Stigma Scale (POSS) has recently been developed to address this issue, but its psychometric properties have gone largely untested. Therefore, this study sought to identify the underlying factor structure and internal consistency of the POSS. This paper used a sample of 135 first responders. Using factor analysis with an orthogonal rotation on Stuart's 11-item POSS, the participant's results revealed two main components, accounting for a total of 72.79% of the overall variance. Factor one is “maltreatment of colleagues with a mental disorder,” and is associated with six of the 11 items on the scale, such as “Most police officers believe that a colleague who has had a mental illness is not trustworthy.” Factor two is “fear of disclosing a mental disorder.” It includes items such as “Most police officers would not disclose to a supervisor/manager if they were experiencing a mental illness.” Findings from this research are similar to the results of previous studies with components such as unwillingness to disclose a mental health condition, fear of how the public will treat an individual with a mental disorder, and anger toward those who decide to seek treatment or get diagnosed with a mental illness. These findings imply that Stuart's POSS is reliable but needs to include two components rather than one. With the two main components, further research can now be conducted to understand why and ultimately mitigate maltreatment or stigma against first responders with a mental health condition.